Synthesis, Crystal Structure, Hydrogen Bonding and Thermal Behaviour of a Three-Dimensional Cu(II)-benzene-1,2,4,5-tetracarboxylate Templated by 1,9-Diaminononane - Köferstein, Roberto; Robl, Christian (Zeitschrift für anorganische und allgemeine Chemie (1950), 2014)
Triclinic single crystals of Cu 4 (H 3 N-(CH 2) 9-NH 3)(OH) 2 [C 6 H 2 (COO) 4 ] 2 ·5H 2 O were prepared in aqueous solution at 80 °C in the presence of 1,9-diaminononane. Space group P (no. 2) with a = 1057.5(2), b = 1166.0(2), c = 1576.7(2) pm, α = 106.080(10)°, = 90.73(2)° and = 94.050(10)°. The four crystallographic independent Cu 2+ ions are surrounded by five oxygen atoms each with Cu-O distances between 191.4(3) and 231.7(4) pm. The connection between the Cu 2+ coordination polyhedra and the [C 6 H 2 (COO) 4 ] 4-anions yields three-dimensional framework with negative excess charge and wide centrosymmetric channel-like voids. These voids extend parallel to [001] with the diagonal of the nearly rectangular cross-section of approximately 900 pm. The channels of the framework accommodate [H 3 N-(CH 2) 9-NH 3 ] 2+ cations and water molecules, which are not connected to Cu 2+. The nonane-1,9-diammonium cations adopt a partial gauche conformation. Thermoanalytical measurements in air show a loss of water of crystallization starting at 90 °C and finishing at approx. 170 °C. The dehydrated compound is stable up to 260 °C followed by an exothermic decomposition yielding copper oxide.